Kinematic Analysis of a Partially Decoupled 3-DOF Parallel Wrist. (23rd November 2015) - Zhang, Fan; Zhu, Yunping; Furukawa, Tomonari; Song, Wanqing
Abstract : A unique spherical parallel wrist with three partially decoupled rotational degrees of freedom (DOFs) is introduced in this paper. The mechanism has the significant advantages of few singularities and simple partially decoupled kinematics. A modified parallel wrist is optimized to have the least link interference workspace. Finally, the decoupled motion is studied in detail to exhibit the kinematic performance of the mechanism.